Determinantes económicos del gasto social en América Latina en el periodo 2000-2019. - Iñamagua Gallo, Gabriela Alexandra (2022)
This research aimed to establish and analyze the main economic determinants of social spending in 14 Latin American countries from period 2000 to 2019. It is from an econometric generalized Least Squares model (GLS) with panel data. The literature suggests that different economic factors determine social spending. Suggested by different sources for the 14 countries to be studied, it is expected to have significant results in all variables such as Democracy (represented by the Democracy Index), Globalization (measured through Foreign Direct Investment), unemployment rate, external debt, tax revenues, trade openness (represented through Imports and Exports), inequality (expressed by the Gini Coefficient), and economic growth (represented through GDP Per Capita). During the nineties, the central governments focused on obtaining social spending growth, implementing different social policies to reduce the existing gap among social classes. When running the econometric model with the established variables and in the determined period, the results present positive coefficients in most variables except for Democracy and unemployment rate, with a probability of 0.53 and 0.64, respectively, thus proceeding to apply a Vector Autoregressive (VAR) model for panel data, demonstrating that the data series presents stationarity in its levels and that in the long term there is no relationship. As for the variables with greater significance, the model suggests that the variable that determines social spending in this study is economic growth (represented by the GDP per capita) and taxation, thus demonstrating that these variables determine social spending.